ปัจจัยที่ส่งผลต่อการตัดสินใจประกอบอาชีพหาบเร่-แผงลอยอาหาร ในเขตเทศบาลนครเชียงใหม่ - อติภาว์ ณ กุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed to investigate the factor affecting the decision of being a food hawker in Chiang Mai Municipality. The objective of this study are the analyze hawker food industry and study the personal factors and socioeconomic factor that affecting of being a food hawker. In order to understand the food operation business, data and information were collected from 200 samples via questionnaires which were distributed to hawker food in Chiang Mai municipality. Chi-Square and Logistic regression model was used to determine factors influencing the decisions of being a food hawker. The Kruskal-Wallis test was used to test about food safety knowledge of food hawker that devided into 4 groups in sub-district of Chiang Mai municipality. Studies have found that most of the food hawker concentrated in eight major markets in Chiang Mai municipality, which were San Pa Khoi Market, Ton Payom Market, Chiang Mai Gate Market, Waroros Market, Mueang Mai Market, Chang Phueak Gate Market, Chiang Mai Gate Market, Ton Lum Yai Market Additional food hawker were concentrated around hospital, school and government facility. Food hawker qenerally prepared ready to cook food.